การมีส่วนร่วมของประชาชนในการจัดทำแผนพัฒนาเทศบาลตำบลพรหมบุรี จังหวัดสิงห์บุรี - สิริพรวุฒิ, ณัฐวัฒน์ (Academic Journal Phranakhon Rajabhat University, 2017)
This survey research set it purposes 1) to study a participation of people in development planning in Phromburi Municipality, Singhaburi Province, 2) to compare an opinion towards a participation of people in development planning in Phromburi Municipality, Singhaburi Province as classify by gender, age, education and occupation, 3) to define problem and suggestion of people regarding participation of people in development planning in Phromburi Municipality, Singhaburi Province. Quantitative data were derived from the people residing in Phromburi Municipality, Singhaburi Province with the total of 23 communities and the Simple Random Sampling technique of Krejcie, R.V. and Morgan, D.W. was utilized with the total of 375 respondents. The research instrument was a rating scale questionnaire with reliability of .89.The statistics used for data analyses were percentage, mean, standard deviation, t-test and F-test (One-way ANOVA). The findings were found that ; 1.Overall aspects of an opinion toward a participation of people in development planning in Phromburi Municipality, Singhaburi Province were at the least level when classified by the least mean score as follows; 1) aspect of beneficial participation, 2) aspect of decision making participation,3) aspect of operational participation, 3) aspect of evaluative participation. 2. There were no significant difference of the opinions regarding to a participation of people in development planning in Phromburi Municipality, Singhaburi Province by demographic factors in all cases. 3.Suggestion and recommendations was there shall be integrated and development plan for career and income generating promotion to the people both production and selling methods. The municipality should be giving an opportunity to the public to participate in their local and community planning and so fort.